2020
DOI: 10.3390/cryst11010010
|View full text |Cite
|
Sign up to set email alerts
|

Response of 4H-SiC Detectors to Ionizing Particles

Abstract: We report the response of newly designed 4H-SiC Schottky barrier diode (SBD) detector prototype to alpha and gamma radiation. We studied detectors of three different active area sizes (1 × 1, 2 × 2 and 3 × 3 mm2), while all detectors had the same 4H-SiC epi-layer thickness of approximately µm, sufficient to stop alpha particles up to 6.8 MeV, which have been used in this study. The detector response to the various alpha emitters in the 3.27 MeV to 8.79 MeV energy range clearly demonstrates the excellent linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
57
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 32 publications
(45 reference statements)
3
57
0
Order By: Relevance
“…This work consolidates some of the most recent findings and revisits some unsolved issues by analyzing the charge-state dependence of transformation, dissociation, and migration of Si-related intrinsic defects in 4H-SiC. Finally, Bernat et al [5] report the response of newly designed 4H-SiC Schottky barrier diode (SBD) detector prototypes to alpha and gamma radiation. A detector resolution of 3% for the wide alpha energy range, combined with the linear response to gamma, yields rates of up to 4.49 Gy/h, demonstrating the usability of this system for the detection of thermal neutrons and gamma decays.…”
supporting
confidence: 62%
“…This work consolidates some of the most recent findings and revisits some unsolved issues by analyzing the charge-state dependence of transformation, dissociation, and migration of Si-related intrinsic defects in 4H-SiC. Finally, Bernat et al [5] report the response of newly designed 4H-SiC Schottky barrier diode (SBD) detector prototypes to alpha and gamma radiation. A detector resolution of 3% for the wide alpha energy range, combined with the linear response to gamma, yields rates of up to 4.49 Gy/h, demonstrating the usability of this system for the detection of thermal neutrons and gamma decays.…”
supporting
confidence: 62%
“…As already described in our previous work [6], a typical 4H-SiC-based detector has the structure of a SBD. Since neutrons can not be directly detected, their presence is deduced from detection of ionizing neutron reaction products, such as alpha particles and tritons.…”
Section: Introductionmentioning
confidence: 97%
“…We have recently demonstrated that simple detection devices based on 4H-SiC Schottky barrier diodes (SBDs), equipped with the thermal neutron converter films, have a measurable neutron response, which varies linearly with the incident neutron flux [1,5]. Moreover, the SiC-based detector response to various alpha emitters demonstrates an excellent linear behavior as a function of detector's active area [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations